Evaluasi Program Kartu Tani dalam Meningkatkan Kesejahteraan Petani Miskin (Studi Kasus di Kelurahan Talotenreng pada BPP Sabbangparu Dinas Pertanian dan Ketahanan Pangan Kabupaten Wajo) - Yusran Yusuf; Bakri Bakri; Erna Erna; Iwan Mamminanga (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to determine the benefits of the farmer card program in improving the welfare of poor farmers in Talotenreng Village at the BPP Sabbangparu of the Wajo Regency Agriculture and Food Security Office and to find out the factors that hinder the evaluation of the farmer card program in improving the welfare of poor farmers in Talotenreng Village at the BPP Sabbangparu of the Wajo Regency Agriculture and Food Security Office. The research method used is a qualitative method, usually the data is inductive or qualitative, and the type of research used is descriptive that provides a detailed picture or phenomenon. The results of this study show that the Farmer Card Program in Talotenreng Village has not been used by farmers as recipients of farmer cards or is still tentative so that farmers cannot feel the benefits, because there are no instructions, directions or orders from the Central Government/Ministry of Agriculture of the Republic of Indonesia. The Farmer Card Program is the latest Government program implemented in all regions with the aim of redeeming the purchase of subsidized fertilizers in an effort to improve the welfare of farmers in accordance with Presidential Regulation No. 77 of 2005 concerning the Determination of Subsidized Fertilizers as Goods in Supervision as amended by Presidential Regulation No. 15 of 2011 concerning Changes in the Determination of Subsidized Fertilizers as Goods Under Supervision.